Universal test panels from a nonmetal for capillary nondestructive testing; Russian Journal of Nondestructive Testing; Vol. 51, iss. 10 - Kalinichenko N. P. Nikolay Petrovich; Kalinichenko A. N. Aleksey Nikolaevich; Lobanova I. S. Irina Sergeevna; Zaytseva A. A. Anna Aleksandrovna (Capillary Methods, 2015)
Title screen